P023: Emergency department data provides a realistic count of pedestrian injuries. (15th May 2017) - Brubacher, J.R.; Sutton, G.; Lam, C.; Trajkovski, A.; Yip, R.; Liu, T.; Chan, H.
Abstract : Introduction: Walking as a form of active transportation is promoted by health professions and environmentalists alike. While the health benefits are indisputable, active transportation is not without risk. Pedestrians are vulnerable road users who often suffer serious injuries especially when involved with collisions with motor-vehicles. While pedestrian injuries involving motor-vehicles are captured in road trauma surveillance systems based on police crash reports, non-collision injuries in this population may be caused by poorly designed infrastructure but are seldom counted as road trauma. This gap hinders road improvement efforts aiming to increase safety for all road users. This study aims to address this knowledge gap. Our objective is to study the profile and circumstances of injuries in pedestrians presenting to ED.Methods: This was a cross-sectional historical chart review study. All injured patients attending our ED are electronically flagged according to mechanism of injury. We reviewed the medical charts of all ED visits flagged as "Pedestrian" or "Fall" to identify all injured pedestrians (defined in this study as anyone walking on a public roadway or getting on/off public transportation). All pedestrian injuries occurred in 2015 were included for chart review.Results: In 2015, a total of 6192 ED presentations were flagged as pedestrian (n=436) or fall (n=5756), and 1108 of these met our inclusion criteria. Of these, 181 (16%) were admitted to hospital. Older pedestrians (≥70 yrs) had a higher hospital admission rate (78/303; 27%) compared to younger ones (<70 yrs: 103/805; 13%). Collision with motor vehicles (MVCs) resulted in only 25% of pedestrian injuries while fall (or tripping) accounted for about 72%. MVC related injuries were more common in younger pedestrians (29% vs 13%) whereas fall related injuries occurred more in older pedestrians (85% vs 67%). The most commonly sustained injuries among the fallers were abrasions followed by fractures.Conclusion: Police crash reports (which capture only MVC related pedestrian injuries) or hospital admission data (which miss those who are treated and released from ED) do not capture all cases of pedestrian injury. ED visit data provides a more realistic count of pedestrian injuries. More pedestrian injuries are caused by falls than by MVCs and policymakers should pay more attention to fall prevention strategies for older pedestrians outside their home environment.